An overview of interventions designed to reduce risk factors for sport injury. Issue 4 (27th March 2011) - McBain, K; Shrier, I; Shultz, R; Meeuwisse, W H; Klugl, M; Garza, D; Matheson, G O
Abstract : Background: While physical activity is associated with an overall reduction in mortality, morbidity and an improved quality of life, it also increases the risk of injury and illness. Objective: To identify gaps in the literature with respect to interventions designed to reduce risk factors for sport injury. Design: Review. Databases: PubMed, Cinahl, Web of Science, Embase, and Sports Discus were searched. Setting: All ages, sex, levels of competition and Olympic sports were included. Main outcome measurement: Pattern of publications over time stratified by study design, intervention type, sport and anatomic site. Results: Only 144 of 2525 articles retrieved by the search strategy met the inclusion criteria. Cross-over study designs increased by 175% since the late 1980's until 2005 but have declined 32% since. Randomised controlled trial (RCT) study designs increased by 650% since the early 1990's. Protective equipment was the focus of 61.8% of the studies and training the remaining 35.4%. Equipment research studied stability devices (83.1%) and attenuating devices (13.5%) while training research studied balance and coordination (54.9%), strength and power (43.1%) and stretching (15.7%). Almost 92.1% of the studies were of the lower extremity and 78.1% were of the joint (non-bone)-ligament type. 57.5% of the reports studied contact sports, 24.2% collision, and 25.75% non-contact sports. Conclusion: We were surprised to find only 144 publications examining interventions designed to reduce risk factors for sport injury. The decrease in cross-over study design and increase in RCTs indicate a shift in research focus. Most notable was the finding that studies using equipment interventions have been decreasing since 2000 (35% decline) while those using training interventions have been increasing (213% increase).